SUPERVISION OF THE PRINCIPAL IN BUILDING THE ACADEMIC CULTURE OF TEACHERS AT SMA 1 SAMATIGA - Mailan Lina; Siti Mayang Sari; Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The research aims to explore the role of the principal as a supervisor in building the academic culture of teachers. The academic culture of teachers has characteristics that are closely related to the actualization of values, orientation, understanding and beliefs of students and all school residents about their dignity and dignity as students. The research method this time uses qualitative methods. Data collection techniques are carried out through observation and interviews. From the two data collected researchers are then analyzed to obtain research findings by reducing data, presenting and then drawing conclusions. The results showed that the role of the principal in building an academic culture requires academic competence in which a principal plans the program, and evaluates the results of the program run by the principal.